Visionary leadership in the administrative staff of the Guapan educational unit - Oscar Martínez Molina (Journal of Technology and Science Education, 2018)
The purpose of the present study lies in determining the visionary leadership manifest in the administrative staff of the Guapan Educational Unit, with the research taking the form of a positivist descriptive research study that will deepen the knowledge of the variable that concerns us: visionary leadership. Through the application of field designs, the information was obtained directly from interaction with the subjects, who made up a population of (62) subjects, among whom were (07) administrators and (55) educational professionals, with the sample consisting of 38 instructors. The instrument used was an 18-item multiple-choice questionnaire (Almost always, Sometimes and Almost never), which was validated by three experts, with a reliability of 0.97, which demonstrates that it is highly reliable. The consolidation of this research showed with its results that the administrative staff engages in visionary leadership in the Guapan Educational Unit. The opinion of the instructional staff, however, shows just the opposite, judging that the administrators show weakness in visionary leadership. For this reason, guidelines are offered to the administrators of the state-funded private school located in the Cañar province, Azogues district, Guapan parish.